A qualitative study of patients’ and caregivers’ perspectives on educating healthcare providers - Adam, Holly; Giroux, Catherine; Eady, Kaylee; Moreau, Katherine (Canadian Medical Education Journal, 2021)
Background: Patients/caregivers can be actively involved in the education of healthcare providers (HCPs). The purpose of this study was to explore patients'/caregivers' perspectives on their involvement and roles in the education of HCPs. Methods: We invited patients/caregivers to participate in one-on-one semi-structured interviews. We analyzed the interview data using conventional content analysis to identify themes. Results: In terms of patient/caregiver involvement in the education of HCPs, we identified that patients/caregivers perceive that it: (a) is challenging because of power-differentials between themselves and HCPs; (b) requires patient training; (c) needs to start early in HCPs’ education processes; (d) can improve patient-HCP partnerships, and (e) requires compensation for patients. With regards to the roles that patients can play in educating HCPs, we found that patients/caregivers want to: (a) teach HCPs about patients’ expectations, experiences and perspectives through case studies, storytelling, and educational research; (b) provide direct feedback to HCPs, and (c) advise on curricula development and admission boards for HCPs. Conclusions: Understanding patients’/caregivers’ perspectives on this topic can help educational leaders and HCPs improve active patient/caregiver involvement in the education of HCPs. We need to listen to patients’/caregivers’ voices in order to make effective changes in current and future health professions education.